PERFORMANCE OF CONCRETE SLABS WITH WASTE MATERIALS: A STUDY USING FINITE ELEMENT ANALYSIS - Yunfei, Wang; Syamsunur, Deprizon; Memon, Zubair Ahmed; Sultan, Basel; Nelfia, Lisa Oksri (Journal of Applied Engineering Science, 2025)
This study investigates the structural behavior of green concrete slabs incorporating waste materials under load conditions using finite element analysis (FEA), aligning with the principles of sustainable construction and responsible consumption and production. The objective is to enhance the mechanical properties of green concrete while reducing carbon dioxide (CO₂) emissions by minimizing cement consumption. Various waste materials, including coconut shells, waste tires, mining byproducts, wastewater treatment sludge, and coastal shells, are evaluated for their potential to improve concrete durability and support circular economy practices. Finite element simulations conducted using Abaqus assess the mechanical performance of these modified concrete slabs. The results indicate significant variations in structural behavior depending on composition. Based on experimental testing and finite element modeling, water treatment sludge concrete (WTSC) exhibited the highest stress response at 0.1016 MPa, while crumb rubber concrete (CRC) recorded the lowest at 0.06044 MPa. Incorporating 3.5% oyster shell waste reduced compressive strength from 36.20 N/mm² to 30.80 N/mm², whereas adding 3.0% coconut fiber reinforcement (CFRC) increased compressive strength to 37.30 N/mm². Among the tested formulations, CRC demonstrated the greatest resistance to external forces in the X, Y, and Z directions. These findings highlight the potential of waste-based concrete mixtures to enhance structural integrity while promoting environmental sustainability. This study reinforces the feasibility of integrating waste materials into concrete as a viable alternative for eco-friendly and climate-resilient infrastructure.